ANALISIS ISU STRATEGIS PENGELOLAAN RUANG PESISIR DI BANDA NEIRA - Refualu, Trixie Dj; Tetelepta, Johannes M S; Abrahamsz, James (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2024)
Coastal areas on small islands provide important services but are very sensitive and vulnerable to natural disasters and pressures from utilization. Future planning and development of coastal areas must still pay attention to the carrying capacity of the space so that the existing potential is not degraded, so it is necessary to have an adaptive spatial management policy to solve problems that focus on preventing strategic issues in the area. This research aims to analyze strategic management issues that include existing conditions, vulnerability and conflict mapping of coastal space utilization. This research was conducted in Banda Neira including Gunung Api Island from March to May 2022. Data collection was carried out through observation, questionnaires and FGDs and analyzed using the Utilization Conflict Matrix. The results show that Banda Neira has a large potential of coastal space and resources that trigger space utilization of 24,629 Ha, coastal space is also vulnerable to potential natural disasters based on the topography of the island and the pressure of human activities. There are differences in the interests of 18 space users and based on conflict mapping there are 57% compatible utilization, 26% cause mild conflict and 17% cause severe conflict. ABSTRAK Wilayah pesisir pada pulau kecil menyediakan jasa penting namun sangat sensitif dan rentan terhadap bencana alam dan tekanan dari pemanfaatan. Perencanaan maupun pengembangan kedepannya terhadap pesisir haruslah tetap memperhatikan daya dukung ruang agar potensi yang ada tidak terdegradasi, sehingga perlu suatu kebijakan pengelolaan ruang yang bersifat adaptif untuk memecahkan masalah yang berfokus pada pencegahan terhadap isu strategis kawasan tersebut. Penelitian ini bertujuan untuk menganalisis isu strategis pengelolaan yang mencakup kondisi eksisting, kerentanan dan pemetaan konflik pemanfaatan ruang pesisir. Penelitian ini dilakukan di Banda Neira termasuk Pulau Gunung Api pada Maret sampai Mei 2022. Pengumpulan data dilakukan melalui observasi, kuesioner dan FGD dan dianalisa menggunakan Matriks Konflik Pemanfaatan. Hasil menunjukan Banda Neira memiliki potensi ruang dan sumberdaya pesisir yang besar sehingga memicu pemanfaatan ruang sebesar 24.629 Ha, ruang pesisir juga rentan terhadap potensi bencana alam berdasarkan topografi pulau dan tekanan kegiatan manusia. Terdapat perbedaan kepentingan 18 pengguna ruang dan berdasarkan pemetaan konflik terdapat pemanfaatan yang 57% cocok, 26% menimbulkan konflik ringan dan 17% menimbulkan konflik berat. Kata Kunci: Wilayah pesisir, penataan ruang, pengelolaan, kerentanan, pemanfaatan